Implementation of Spbe Policy in Employment Services in Bogor City - Khan, Sahib; Sartika, Ika (Ridwan Institute, 2025)
The Government of Indonesia has established the Electronic-Based Government System (SPBE) policy through Presidential Regulation No. 95 of 2018 as a digital transformation initiative in governance. This policy aims to achieve effective, efficient, transparent, and accountable government, while improving the quality of public services. This study examines the implementation of the SPBE policy in labor services in the City of Bogor using a qualitative approach based on literature review and document analysis. The findings indicate that the Bogor City Government has adopted SPBE in the labor sector by developing the “BogorKerja” employment information system, which provides a job vacancy portal, online issuance of job seeker cards (AK1), and integration with national platforms (the Ministry of Manpower’s KarirHub). Labor-related licensing services and administrative processes have also been digitalized, for example through e-ticket services for AK1 processing and the use of online applications. Furthermore, Bogor City launched the digital platform “Bogor Single Window (BSW)” as a super-app integrating various public services – including employment services – accessible with a single login. This implementation is supported by the City’s Manpower Office as a key actor in verifying data, facilitating hybrid job fairs, and coordinating with central agencies. Nevertheless, challenges remain, such as cross-system integration, improving personnel IT competencies, ICT infrastructure, and user outreach. Innovations undertaken, such as e-ticketing, job-matching portals, and central-local service integration, have enhanced service efficiency. The study concludes that SPBE implementation in Bogor’s labor services has progressed in line with national policy, though continuous efforts in infrastructure enhancement, human resource capacity, and user adoption are needed to fully realize SPBE objectives.